2001
DOI: 10.1079/phn2001132
|View full text |Cite
|
Sign up to set email alerts
|

Serum carotenoids and radiographic knee osteoarthritis: the Johnston County Osteoarthritis Project

Abstract: Objective: Antioxidant intake has been associated with less progression of radiographic knee osteoarthritis (OA), but studies of carotenoid biomarkers and OA have not been done. We examined associations between serum concentrations of nine naturally occurring carotenoids and radiographic knee OA. Design: The study design was matched case±control. Sera were analysed by highperformance liquid chromatography for nine carotenoids: lutein, zeaxanthin, a-and b-cryptoxanthin, trans-and cis-lycopene, a-carotene, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 30 publications
3
14
0
Order By: Relevance
“…The Framingham OA Cohort Study showed that β-carotene intake reduced the risk of progression of knee OA [ 7 ]. A case–control study performed by De Roos and colleagues, however, found that those in the highest tertile of serum lutein or β-cryptoxanthin were less likely to have knee OA than controls, and those in the highest tertile of serum β-carotene or zeaxanthin were more likely to have knee OA [ 28 ]. In contrast, our study found that the lutein and zeaxanthin intake was associated with a decreased risk of cartilage defects, and that β-cryptoxanthin intake was associated with a decreased tibial plateau bone area – both suggesting a beneficial effect on the knee.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Framingham OA Cohort Study showed that β-carotene intake reduced the risk of progression of knee OA [ 7 ]. A case–control study performed by De Roos and colleagues, however, found that those in the highest tertile of serum lutein or β-cryptoxanthin were less likely to have knee OA than controls, and those in the highest tertile of serum β-carotene or zeaxanthin were more likely to have knee OA [ 28 ]. In contrast, our study found that the lutein and zeaxanthin intake was associated with a decreased risk of cartilage defects, and that β-cryptoxanthin intake was associated with a decreased tibial plateau bone area – both suggesting a beneficial effect on the knee.…”
Section: Discussionmentioning
confidence: 99%
“…Although serum measures reflect the dietary intake of the carotenoids, they also reflect differences in interindividual absorption and metabolism. Moreover, when examining the effect of carotenoid intake on the knee, we used a more sensitive method of assessing knee structure than the Framingham study and De Roos and colleagues' study, which used radiographic assessment of the knee joint [ 7 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using serum biomarkers of antioxidant status, Jordan and colleagues [42] reported that the relative frequencies of isoforms of tocopherols might be important in OA, showing that subjects in the Johnston County Osteoarthritis Project who had a high ratio of alpha:gamma tocopherol were 50% less likely to have radiographic knee OA. In the same study, those in the highest tertile of serum lutein and beta-cryptoxanthine also were less likely to have radiographic knee OA [43]. Subjects who had low levels of selenium, another anti-oxidant measured in toenails, were more likely to have radiographic knee OA, bilateral knee OA, and severe knee OA [44].…”
Section: Systemic Risk Factors For Osteoarthritismentioning
confidence: 99%
“…The Framingham OA Cohort Study revealed that intake of beta-carotene was associated with reduction of progression of symptomatic knee OA 6 . Another study presented participants with increased levels of serum lutein or beta-cryptoxanthin developed knee OA to a lesser degree, on the contrary, it was more possible participants with the highest concentrations of serum beta-carotene or zeaxanthin to develop knee OA 40 .…”
Section: Antioxidantsmentioning
confidence: 99%